2016
DOI: 10.1017/jfm.2016.536
|View full text |Cite
|
Sign up to set email alerts
|

Linear modal instabilities of hypersonic flow over an elliptic cone

Abstract: Steady laminar flow over a rounded-tip $2\,:\,1$ elliptic cone of 0.86 m length at zero angle of attack and yaw has been computed at Mach number $7.45$ and unit Reynolds number $Re^{\prime }=1.015\times 10^{7}~\text{m}^{-1}$. The flow conditions are selected to match the planned flight of the Hypersonic Flight Research Experimentation HIFiRE-5 test geometry at an altitude of 21.8 km. Spatial linear BiGlobal modal instability analysis of this flow has been performed at selected streamwise locations on planes no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 52 publications
7
49
0
Order By: Relevance
“…The evolution of disturbances in incompressible flows is characterised by the kinetic energy of the disturbances, which is commonly used to define the norm for the energy of disturbances. However, in compressible flows fluctuations of thermodynamic quantities contribute to the energy and need to be included (Mack 1984;Hanifi, Schmid & Henningson 1996;Freund & Colonius 2002;Tumin & Reshotko 2003;Ray, Cheung & Lele 2009;Paredes et al 2016); hence, the energy of the disturbances also known as the Mach energy norm is defined as…”
Section: Nonlinear Spatial Growth From Lesmentioning
confidence: 99%
“…The evolution of disturbances in incompressible flows is characterised by the kinetic energy of the disturbances, which is commonly used to define the norm for the energy of disturbances. However, in compressible flows fluctuations of thermodynamic quantities contribute to the energy and need to be included (Mack 1984;Hanifi, Schmid & Henningson 1996;Freund & Colonius 2002;Tumin & Reshotko 2003;Ray, Cheung & Lele 2009;Paredes et al 2016); hence, the energy of the disturbances also known as the Mach energy norm is defined as…”
Section: Nonlinear Spatial Growth From Lesmentioning
confidence: 99%
“…More recent DNS simulations of Dinzl & Candler (2017) showed a difference between the centreline system of vortices and the crossflow vortices generated by surface roughness. Recent studies based on BiGlobal linear stability analysis (Paredes & Theofilis 2015;Paredes et al 2016d ) conducted on the HIFiRE-5 geometry confirmed the dominant role played by the crossflow instabilities in the offcentreline region, as well as the presence of different instability modes occurring along the centreline bulge, as was first identified by Choudhari et al (2009). These centreline modes can explain the strong disturbance growth observed in the computations of Bartkowicz et al (2010) along the centreline.…”
Section: Introductionmentioning
confidence: 69%
“…Recent studies based on BiGlobal linear stability analysis [39,40] conducted on the HIFiRE-5 geometry confirmed the dominant role played by the crossflow instabilities in the off-centerline region, but showed also that different instability modes (denoted centerline modes) may occur along the centerline, which can significantly affect transition.…”
Section: Introductionmentioning
confidence: 99%